Study on the Synergistic Promotion of NOx Reduction in Coal Combustion by CaO and Cu-TiO2 - Wang Shuqin; Zhang Hao; Cao Shuai; Fu Hao (E3S Web of Conferences)
In order to mitigate the emissions of NOx, SO2, and other harmful gases generated from coal combustion, as well as to achieve simultaneous desulfurization and denitrification during the combustion of medium- and high-sulfur coal, Cu-TiO2 was synthesized using a microwave-sol-gel method. CaO and Cu-TiO2 were ground together and mixed with experimental coal as additives. The experiments were conducted under an oxygen flow rate of 40 mL/min at a temperature of 850°C. The results show that the removal rates of SO2 and NOx are as high as 89.10% and 48.48%, respectively, while the amount of catalyst used constituted only 6% of the mass of coal. Characterization and analysis of the reactants were performed; XRD and BET results demonstrated that upon adding Cu in its +2 valence state, there is a notable alteration in the surface structure of TiO2 crystals: an increase in anatase crystal content, enhancement in specific surface area, reduction in particle size, augmentation of O2 adsorption sites, improved crystallinity, all contributing to heightened catalytic activity. The activation effect on TiO2 by CaO was confirmed through infrared spectrum analysis; both components exhibited synergistic effects during coal combustion reactions. Specifically, CaO facilitated denitrification processes involving TiO2 while TiO2 enhanced desulfurization activities associated with CaO. TG analysis further validated the combustion-supporting role played by Cu-TiO2. Additionally, XRF analyses indicated that incorporating Cu-TiO2 can enhance slagging behavior within coal ash. The plan can be applied in coal-fired power plants in the future that use complex and variable coal types in order to reduce production costs, save energy and pollution, and conserve resources.